Frameplay : o ato configurativo de jogo nos modos fotografia da série gran turismo - Fontoura, Mariana Gomes da (2023)
This thesis is based on the phenomenon of in-game photography, focusing on the emergence of the so-called "photo mode" in digital games and virtual photographic cameras. It proposes an investigation into how the presence of these cameras alters the gameplay dynamics between operator and machine within the action spaces of the game world. Inspired by the Grounded Theory of Glaser and Strauss (1967) and the readings of other researchers about this methodology (CORBIN; STRAUSS, 1990; GOULDING, 1999; GLASER; HOLTON, 2004; CHARMAZ, 2009; FRAGOSO; RECUERO; AMARAL, 2011; HOOK, 2015), the study sectioned into five chapters. In the first two, it develops the presentation and contextualization of the theme with state-of-the-art and methodological path, respectively. In addition to the methodology, chapter two also presents a mapping of games with photography mode from 2004 to 2020, as well as the open, axial and selective encoding of the material collected. In the third chapter, the approaches of contemporary photography (FATORELLI, 2019; DUBOIS, 2019) are crossed with the phenomenon of in-game photography and the perspectives of studies already developed (POREMBA, 2007; GIDDINGS, 2013; GERLING, 2018; MÖRING; MUTIIS, 2019; PAULA, 2021; RIZOV, 2021). In the fourth chapter, questions about the game world (ADAMS, 2010; GALLOWAY, 2006; JØRGENSEN, 2014; NITSCHE, 2008) and virtual cameras in games lead the reflection to the spaces of action and the way these cameras are studied by other theorists (GIDDINGS, 2013; MITCHELL, 2001; NITSCHE, 2008). The last chapter is sectioned into three moments: the presentation of the game series, which composes the analyzed corpus, followed by the descriptive exploration of the photography modes and virtual cameras of Gran Turismo 4, 5, 6 and Sport, ending with the theoretical codification. The resulting proposal from this path is the notion of "frameplay": gameplay dedicated to the photographic configurative act through the photo mode and the configuration of virtual photographic camera parameters in different spatialities in the analyzed games.